Modification of T cell receptor beta chain gene: the J2 region but not the J1 region of the T cell receptor beta chain gene is hypomethylated in human B cells and monocytes. - Sakamoto, S (1988)
In order to determine the relationship between the generation of a 1.0 kb mRNA and methylation of the T cell receptor beta chain gene, we have analyzed the methylation state of the T cell receptor beta chain gene (T beta) in monocyte and B cell DNA, focusing on the J1 and J2 regions of this gene in human genomic DNA. We have observed that a portion of the J2 region of T beta rich with CpG sequences is nonmethylated in both monocyte and B cell DNA but that the J1 region is methylated in both cell DNAs. We suggest that the hypomethylation of the J2 region constitutes a condition in which a 1.0 kb truncated mRNA of the beta chain gene is expressed in B cells. We have also found that the CpG sequence 1.0 kb 3' to the last exon of the J2 was totally nonmethylated in B cell DNA but methylated in half of monocyte DNA. This difference in methylation between monocyte and B cell DNA may reflect the differential transcriptional activity in monocytes and B cells of a 1.0 kb mRNA of T beta.